Four-point vaginal reconstruction versus conventional suturing techniques for the treatment of congenital vaginal atresia: a prospective randomized controlled trial - Shang, Xianhui; Liu, Yuanmei; Zhang, Zhendong; Zhou, Guangxu; Tan, Hongyang; Li, Yingbo; Mao, Kaiyi; Luo, Zhen (Frontiers in Pediatrics, 2025)
BackgroundCongenital vaginal atresia is a rare developmental anomaly in which the vagina is partially or completely replaced by fibrous tissue despite normal uterine and ovarian development. Surgical reconstruction is the only effective treatment, and the choice of technique may critically influence outcomes. This study compared the clinical effectiveness of four-point vaginal reconstruction with conventional suturing.MethodsA prospective, randomized controlled trial was conducted at the Affiliated Hospital of Zunyi Medical University. Eligible patients diagnosed with congenital vaginal atresia were stratified by atresia type (distal, proximal, or complete) and randomly assigned to undergo either four-point vaginal reconstruction or conventional suturing. The predefined primary endpoints were operative duration, postoperative complications, functional recovery, and patient-reported satisfaction.ResultsA total of eighty-three patients were enrolled. Forty-two were assigned to the four-point reconstruction group and forty-one to the conventional suturing group. Operative duration was significantly shorter in the four-point group compared with the conventional group (45.3 ± 12.7 vs. 65.4 ± 15.6 min; P < 0.05). No cases of vaginal stenosis were observed in the four-point group, whereas five occurred in the conventional group. Vaginal depth and functional recovery rates were higher in the four-point group, although differences did not reach statistical significance. Patient-reported outcomes, including FSFI domain scores (desire, arousal, orgasm, satisfaction) and SF-36 quality-of-life measures, were consistently higher in the four-point group, with several domains achieving statistical significance (P < 0.05).ConclusionsFour-point vaginal reconstruction may offer clinical advantages over conventional suturing techniques in the surgical management of congenital vaginal atresia. The technique was associated with shorter operative time, fewer complications, and improved functional and patient-reported outcomes. However, as a single-center study with a moderate sample size, these findings warrant further validation in larger, multicenter cohorts.